2012
DOI: 10.2105/ajph.2011.300601
|View full text |Cite
|
Sign up to set email alerts
|

Under the Radar: How Unexamined Biases in Decision-Making Processes in Clinical Interactions Can Contribute to Health Care Disparities

Abstract: Several aspects of social psychological science shed light on how unexamined racial/ethnic biases contribute to healthcare disparities. Biases are complex but systematic, differing by racial/ ethnic group and not limited to love–hate polarities. Group images on the universal social cognitive dimensions of competence and warmth determine the content of each group’s overall stereotype, distinct emotional prejudices (pity, envy, disgust, pride), and discriminatory tendencies. These biases are often unconscious an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
256
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 302 publications
(262 citation statements)
references
References 93 publications
3
256
1
2
Order By: Relevance
“…However, implicit bias requires a longer period before a shift is noted [10,11]. Our results followed a similar pattern, where overt discrimination against LGBT individuals was low in prevalence, while measures of the inclusiveness of the environment showed that there is room for improvement.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…However, implicit bias requires a longer period before a shift is noted [10,11]. Our results followed a similar pattern, where overt discrimination against LGBT individuals was low in prevalence, while measures of the inclusiveness of the environment showed that there is room for improvement.…”
Section: Discussionsupporting
confidence: 75%
“…This has been accompanied by a significant decline in explicit bias (discrimination, hate speech) and negative attitudes towards sexual and gender minorities [9]. With shifts in society’s attitude towards minorities, explicit bias becomes socially unacceptable, while implicit bias remains widespread [10,11]. Implicit bias refers to individuals’ perception and stereotypes without conscious intention.…”
Section: Introductionmentioning
confidence: 99%
“…Research has been consistently demonstrating that weight discrimination is associated with eating disordered attitudes and behaviors (Durso, Latner, & Hayashi, 2012;Puhl & Latner, 2007), avoidance of physical activity (e.g., Faith, Leone, Ayers, Heo, & Pietrobelli, 2002), psychopathological symptoms (e.g., Ashmore, Friedman, Reichmenn, & Musante, 2007;Puhl & Heuer, 2009), poorer health care, reduced treatment compliance, medical care avoidance (Dovidio & Fiske, 2012;Lillis, Hayes, Bunting, & Masuda, 2009;Puhl & Heuer, 2010) and may lead to weight gain (Sutin & Terracciano, 2013). Weight stigma may even hold a negative impact on the efficacy of weight loss treatments (Carels, et al, 2009;Puhl & Heuer, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…[26][27] In addition to these processes, LGBT employees may face forms of disadvantage that arise out of pressures to "pass" as heterosexual, go "stealth" (transgender individuals who hide their transgender status) or otherwise "cover" (or downplay) their LGBT status out of fear of negative repercussions at work. [28][29] Passing or going stealth does not inoculate LGBT employees from negative workplace experiences, however.…”
Section: Introductionmentioning
confidence: 99%